2002
DOI: 10.1023/a:1019892310988
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Overnight low-temperature exposure inhibits photosynthesis in chilling-sensitive species, such as tomato and cucumber, by as much as 60%. Earlier work showed that low temperature stalled the endogenous rhythm controlling transcription of certain nuclear-encoded genes in chilling-sensitive plants causing the synthesis of the corresponding transcripts and proteins to be mistimed upon rewarming. The activity of nitrate reductase (NR), the first and rate-limiting step in the assimilation of nitrate into amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It is found that the nonlinear term −b(ξ ′ ) 2 has the effects of strongly enhancing ξ(r) on small scales, and making P (k) flatter in k < k 0 . The friction term aξ ′ has the following effects: slightly increasing the height of ξ(r) on small scales; moving the zeros of ξ(r) to larger r; strongly damping the amplitude of oscillations of ξ on large scales [4,37,12,13,14,35], as seen in FIG.7; smoothing out the sharp peak of P (k) at k 0 and turning P (k) positive for k < k 0 . The main conclusion of this paper is the following.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the nonlinear term −b(ξ ′ ) 2 has the effects of strongly enhancing ξ(r) on small scales, and making P (k) flatter in k < k 0 . The friction term aξ ′ has the following effects: slightly increasing the height of ξ(r) on small scales; moving the zeros of ξ(r) to larger r; strongly damping the amplitude of oscillations of ξ on large scales [4,37,12,13,14,35], as seen in FIG.7; smoothing out the sharp peak of P (k) at k 0 and turning P (k) positive for k < k 0 . The main conclusion of this paper is the following.…”
Section: Discussionmentioning
confidence: 99%
“…where n is the spatial number density. This result qualitatively explains several observed features, such as a stronger correlation for more massive galaxies, galaxies with a smaller n having a higher P (k) [10,14], the scaling of "correlation length" r 0 with the mean cluster separation d as r 0 (d) ∝ d 0.3∼0.5 [1,2,8,17,41], and damped oscillations of ξ c (r) for clusters with a wave-length 2π/k 0 ≃ 120 h −1 Mpc [4,12,13,14,37,35]. Here one sees the physical meaning of the sound speed c s .…”
Section: Analytic and Numerical Solutionmentioning
confidence: 99%
“…It is also fairly well established that red galaxies are generally more clustered than the blue population (Landy, Szalay & Koo 1996; Tucker et al 1997), but a quantitative comparison is more difficult, because most of the values in the literature are obtained from the angular or redshift space correlation functions, and a variety of colour bands are used. Willmer et al (1998) quote a relative variance bias in real space at 8 h −1 Mpc, and suggest that there is evidence for scale dependence in the relative bias.…”
Section: Biasing Of Haloes and Galaxiesmentioning
confidence: 99%
“…The SDSS LRG sample will also be useful to verify the presence of baryonic features, in P (k), due to oscillations in the baryonic component within the last-scattering surface [42]. A possible detection has been claimed in an analysis of some [56] and SDSS [57] data, compared to the previous Las Campanas Redshift Survey [58]. The dotted lines show instead a correlation function in real space, obtained through deprojection from the APM 2D galaxy catalogue [59] under two different assumptions about galaxy clustering evolution.…”
Section: The Power Spectrum Of Fluctuationsmentioning
confidence: 97%
“…Fig. 4 shows the correlation function measured in redshift space, ξ(s) (see next section for definitions), from the 2dF and SDSS current data sets [56,57], compared to the previous LCRS [58]. Also shown (dotted lines) is ξ(r) reconstructed from the APM angular survey [59].…”
Section: The Two-point Correlation Functionmentioning
confidence: 99%